ANALISIS RASIO DAN ECONOMIC VALUE ADDED (EVA) UNTUK MENILAI KINERJA KEUANGAN PT. HM. SAMPOERNATBK. TAHUN 2014 - 2016 - Yuliyanto, Wakhid; Rafingki, Firgian (Politeknik Dharma Patria Kebumen, 2019)
This purpose of this research is to identify the  financial performance based on the result of calculation Analisys Ratio and Economic Value Added ( EVA ) in the financial report of PT. HM. Sampoerna Tbk period 2014 ? 2016 because of in every annual report there was un explaining how condition of financial performance of this company .This research it is a quantitative descriptive research. The method used was Analysis Ratio and Economic Value Added (EVA). Analysis Ratio used was Liquidity Ratio (Current Ratio,Quick Ratio,Cash Ratio), Solvability Ratio (Debt to Assests Ratio, Debt to Equity Ratio), Activity Ratio (Inventory Turn Over Ratio, Total Assets Turn Over) and Profitability Ratio (Return On Assest, Return On Equity). For the result of the calculation Analysis Ratio the company in condition good condition of the financial performance if  assess from Liquidity Ratio, Solvability Ratio, Activity Ratio and Profitability Ratio because of the result was over average of a kind industry. Meanwhile the result which is used was EVA in period 2014 ? 2016 the result all of them positive value which mean there is value added which is  indication PT. HM. Sampoerna Tbk in good condition of the financial performance. Based on result of the analysis overall financial performance of PT. HM. Sampoerna Tbk. in 2014 ? 2016 is good with revenue increase every year. However the company has not maximized fund resources to making a profit.